2022
DOI: 10.15562/bmj.v11i3.3537
|View full text |Cite
|
Sign up to set email alerts
|

The effect of discharge planning on the stability of blood sugar levels in type 2 diabetes mellitus patients

Abstract: Introduction: Diabetes mellitus (DM) is a serious threat to human health in the 21st century, Indonesia as a developing country has a high number of sufferers. This study aims to analyze the effect of discharge planning on the stability of blood sugar levels in type 2 patients. Methods: The design of this study was a Quasi-Experimental Pre and Post-test with a Control Group. The population in this study were all patients with type 2 DM, a large sample of 54 respondents, taken by purposive sampling technique. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Patient education in managing diabetes mellitus is one of the important pillars for optimizing medical therapy. If education is effective, self-management and increased adherence to health worker recommendations will be carried out (Bistara et al, 2022). Based on the research of (Cuevas et al, 2022) results described above, DSME can reduce Blood glucose levels through self-care.…”
Section: Resultsmentioning
confidence: 99%
“…Patient education in managing diabetes mellitus is one of the important pillars for optimizing medical therapy. If education is effective, self-management and increased adherence to health worker recommendations will be carried out (Bistara et al, 2022). Based on the research of (Cuevas et al, 2022) results described above, DSME can reduce Blood glucose levels through self-care.…”
Section: Resultsmentioning
confidence: 99%
“…This study suspected the possibility of death caused by complications or exacerbation due to comorbid causes, which iss also supported in previous studies. 18 In addition, it was found that some patients did not perform routine control for their comorbid diseases, thereby increasing the risk of patient mortality. The existence of a drug supervisor for patients with comorbidities is needed to help with routine control to reduce the risk of patient mortality if exposed to COVID-19.…”
Section: Discussionmentioning
confidence: 99%